2017
DOI: 10.1111/joa.12651
|View full text |Cite
|
Sign up to set email alerts
|

A 3D musculoskeletal model of the western lowland gorilla hind limb: moment arms and torque of the hip, knee and ankle

Abstract: Three‐dimensional musculoskeletal models have become increasingly common for investigating muscle moment arms in studies of vertebrate locomotion. In this study we present the first musculoskeletal model of a western lowland gorilla hind limb. Moment arms of individual muscles around the hip, knee and ankle were compared with previously published data derived from the experimental tendon travel method. Considerable differences were found which we attribute to the different methodologies in this specific case. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 84 publications
(285 reference statements)
1
19
0
Order By: Relevance
“…The constant in this equation is specific muscle tension. Similar values were used in other studies on musculoskeletal models in vertebrates, including hominoids (Goh et al, 2017; Hutchinson et al, 2015; O'Neill et al, 2013; Umberger et al, 2003). However, different equations were used to calculate the MTU properties in the human shoulder model that we use for comparison (Nikooyan et al, 2011).…”
Section: Methodsmentioning
confidence: 90%
“…The constant in this equation is specific muscle tension. Similar values were used in other studies on musculoskeletal models in vertebrates, including hominoids (Goh et al, 2017; Hutchinson et al, 2015; O'Neill et al, 2013; Umberger et al, 2003). However, different equations were used to calculate the MTU properties in the human shoulder model that we use for comparison (Nikooyan et al, 2011).…”
Section: Methodsmentioning
confidence: 90%
“…Conclusively, impingement and dislocation are associated with parts of excessive small parameters of HROMs that are determined by inclination and anteversion of cups. The ways to study HROMs include cadaver study, CT three-dimension reconstruction, and skeletal muscle model ( Martin et al, 2008 ; Mccarthy et al, 2016 , 2017 ; Ezquerra et al, 2017 ; Goh et al, 2017 ; Jamari et al, 2017 ; Ohmori et al, 2017 ; Sonntag et al, 2017 ). Using cadaveric hip, Martin ( Martin et al, 2008 ) demonstrated not only the impingement between bones or prostheses but also the limitations among ligaments, muscle, and capsule, which reflected the real situation of dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…This method is highly repeatable but lacks the effect of soft tissue. The skeletal muscle model reconstructs both bones and soft tissues, such as joint capsules, muscles, and ligaments ( Goh et al, 2017 ). It can predict the role of soft tissue in hip dislocation, but the soft tissue assessment by finite element analysis is very complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Hip extension capability was essentially human-like in Australopithecus afarensis and Australopithecus africanus, suggesting an economical walking gait but reduced mechanical advantage for powered hip extension during climbing.’ Contra Lovejoy et al (2016) who unequivocally attribute a short ischium in Homo to running, Kozma et al (2018) demonstrate that a short ischium greatly enhances distance travelled for energy consumed in walking. But it is worth noting that musculoskeletal modelling by some of us (Goh et al, 2017) showed that in terms of joint moments and torques exerted by all major lower limb extrinsic muscles, the ability of gorillas to walk bipedally is not limited by their adaptations for quadrupedalism and vertical climbing.…”
Section: Functional Interpretationmentioning
confidence: 99%